2022
DOI: 10.3892/etm.2022.11128
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin reduces cardiomyocyte apoptosis from mitochondrial release of cytochrome c to improve doxorubicin‑induced cardiotoxicity

Abstract: Doxorubicin (DOX) has powerful anticancer properties, but its clinical application is affected by its serious cardiotoxicity. Wogonin (WG) has been shown to have marked cardiovascular protection potential. However, it is not known whether this potential can protect the heart from DOX damage. The aim of the present study was to investigate whether WG could ameliorate the cardiotoxicity of DOX. DOX and WG were used to establish a model of cardiac damage. Echocardiography, brain natriuretic peptide, creatine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…(3) Caspases are enzymes that play a role in programmed cell death. Studies have shown that treatment with Dox can activate the apoptosis regulators, resulting in the activation of caspase-3 in cardiac muscle, leading to cell death [99]. Consistent with this, inhibiting caspase-3 activity can help to reduce the cardiotoxiceffects of Dox [100].…”
Section: Metforminmentioning
confidence: 82%
“…(3) Caspases are enzymes that play a role in programmed cell death. Studies have shown that treatment with Dox can activate the apoptosis regulators, resulting in the activation of caspase-3 in cardiac muscle, leading to cell death [99]. Consistent with this, inhibiting caspase-3 activity can help to reduce the cardiotoxiceffects of Dox [100].…”
Section: Metforminmentioning
confidence: 82%
“…We expected that a dose of 15 mg/kgbw of doxorubicin would be insufficient to convert into doxorubicinol or carbonyl reductase 3, already inhibited by the polyphenol component in Vernonia amygdalina. Apoptosis has been identified as a vital process for maintaining balanced cell development [29]. However, it has been extensively observed that aberrant cell signaling is associated with a disturbed apoptotic balance, leading to cancer growth and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [ 28 ] used H9c2 cells and discovered that the noncoding repressor of nuclear factor of activated T cells up-regulated the expression of si-hypoxia-inducible factor-1 alpha (HIF-1 alpha), thereby alleviating cardiomyocyte apoptosis induced by hypoxia/ reoxygenation (H/R). Wei et al [ 29 ] employed Doxorubicin (DOX) to establish a rat heart injury model and found that Wogonin protected the rat heart from DOX-induced damage by inhibiting the release of mitochondrial cytochrome c and reducing the apoptosis of cardiomyocytes caused by caspase activation. Xu et al, [ 30 ] utilizing male C57/B6J mice, found that Shenfu injection up-regulated the expression of B-cell lymphoma-2 (Bcl-2) protein, thereby inhibiting myocardial apoptosis and mitigating mitochondrial damage induced by septicemia through downregulation of BH3 interacting domain death agonist and caspase-9 proteins.…”
Section: Discussionmentioning
confidence: 99%